206k views
3 votes
I have no clue on how to do this someone help me out

I have no clue on how to do this someone help me out-example-1
User Guanhuiwit
by
5.2k points

2 Answers

4 votes

Answer:

15

Explanation:

Numerator ; 4(X+5)(X+1)

substitute : X=5

The first expression becomes : 4(5+5)(5+1)

= 4(10)(6)

=4×10×6

=240

Denominator : (X+3)(x-3)

substitute: X=5

=(5+3)(5-3)

=(8)(2)

=16

Now, Dividing the numerator by the denominator we have 240÷16=15

User David Mabodo
by
4.7k points
5 votes

Answer:

B

Explanation:

Substitute x = 5 into the expression


(4(5+5)(5+1))/((5+3)(5-3))

=
(4(10)(6))/(8(2))

=
(240)/(16)

= 15 → B

User Eugeny Pavlenko
by
5.3k points